2015
DOI: 10.1055/s-0035-1546956
|View full text |Cite
|
Sign up to set email alerts
|

Annulus Fibrosus Can Strip Hyaline Cartilage End Plate from Subchondral Bone: A Study of the Intervertebral Disk in Tension

Abstract: Study Design Biomechanical study on cadaveric spines. Objective Spinal bending causes the annulus to pull vertically (axially) on the end plate, but failure mechanisms in response to this type of loading are poorly understood. Therefore, the objective of this study was to identify the weak point of the intervertebral disk in tension. Methods Cadaveric motion segments (aged 79 to 88 years) were dissected to create midsagittal blocks of tissue, with ∼10 mm of bone superior and inferior to the disk. From these bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 37 publications
(53 reference statements)
2
13
0
Order By: Relevance
“…33 Failure stresses and failure locations measured in the current study were consistent with those found in previous human disc-bone tensile tests. Our measured failure stresses (range: 0.22-0.93 MPa) were within the range of those reported by Balkovec et al 11 (range: 0.14-2.8 MPa) and lower than those found by Green et al 18 (average 1.7 MPa for posterior and 3.8 MPa for AA), presumably because we cut our specimens smaller to isolate more specific regions, thus disrupting the collagen network mid-fiber due to the angled orientation of annulus fibers. The higher modulus of the PA compared to the AA may help to resist forward bending movements, but the lower extensibility may put weak EPJs at risk for herniation.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…33 Failure stresses and failure locations measured in the current study were consistent with those found in previous human disc-bone tensile tests. Our measured failure stresses (range: 0.22-0.93 MPa) were within the range of those reported by Balkovec et al 11 (range: 0.14-2.8 MPa) and lower than those found by Green et al 18 (average 1.7 MPa for posterior and 3.8 MPa for AA), presumably because we cut our specimens smaller to isolate more specific regions, thus disrupting the collagen network mid-fiber due to the angled orientation of annulus fibers. The higher modulus of the PA compared to the AA may help to resist forward bending movements, but the lower extensibility may put weak EPJs at risk for herniation.…”
Section: Discussionsupporting
confidence: 91%
“…Historical data suggest structural weakness at the cartilage-vertebral EPJ, as supported by recent work showing this location as the weak link of the disc-vertebra interface. 11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our preliminary findings suggest that lack of integration, especially at the CEP-VEP interface, is associated with IVD degeneration and adds to the current knowledge within the field, whereby lack of structural integrity at the CEP-VEP junction is increasingly being implicated in the aetiology of herniations [31], [20], [40], [16], [3]. Possible reasons for reduced connectivity at the CEP-VEP junction may be either an increase in marrow spaces abutting this interface [18], so reducing locations where fibre integration is possible or retention of discontinuities in the endplate following insufficient retraction of the notochord during spinal development [8].…”
Section: Discussionmentioning
confidence: 85%
“…Possible reasons for reduced connectivity at the CEP-VEP junction may be either an increase in marrow spaces abutting this interface [18], so reducing locations where fibre integration is possible or retention of discontinuities in the endplate following insufficient retraction of the notochord during spinal development [8]. A further reason could be due to actual physical disruption, as has been described in a recent biomechanical study in which the IVD was subjected to loading in tension such as might be experienced during spinal bending [3]. Indeed, the mechanism by which these two tissues are secured together may be more reliant on the rigid inorganic fraction present in the tissues instead of the soft non-mineralised organic fraction.…”
Section: Discussionmentioning
confidence: 99%